O controle da hanseníase em São Paulo: Departamento de Profilaxia da Lepra (1930-1969) - Silva, Elisandra Gasparini (2018)
This research aims to understand the role played by the Department of Leprosy Prophylaxis, created in 1935 and extinguished in 1967 and which was responsible for the policy of isolation practiced in the network of five asylum-colonies in São Paulo and for the practices that occurred during those years. During this period, people with leprosy lost not only their individuality and their right to come and go, but also the society and the transformations that took place in it. Although there was a decree from 1962 that determined the end of this practice with Hansen's disease patients, the state of São Paulo would maintain it until 1967, when the São Paulo Health Secretariat was restructured. The initial date of the periodization contemplates the first ideas about the isolation of the patients and the construction of the asylum-colonies, until the impact of these changes in the reform of 1969 imposed by the State Secretariat of Health of the State of São Paulo